Quality assessment of pre- and postnatal nutrition and exercise mobile applications in the United States and China - Yu, Hongli; He, Juan; Li, Keqiang; Qi, Wen; Lin, Jiahui; Szumilewicz, Anna (Frontiers in Nutrition, 2023)
Background: Mobile applications (apps) are becoming increasingly prevalent as tools for improving maternal health behaviors. However, the recently updated content and quality of these apps remain unknown. This research investigated the fundamental characteristics, functional modules, and overall quality of maternal apps available in the United States and China to reveal critical nutrition and physical activity gaps. Methods: A systematic search was performed in Android and iOS app stores (China and the United States). Apps were eligible if they targeted pregnant or postpartum women, focused on nutrition or physical activity, and had interfaces in English or Chinese. The basic characteristics, functional modules, and overall quality of the apps were evaluated, and differences between apps available in China or the United States were determined using analysis of variance and chi-square tests. Pearson correlations were utilized to investigate links between objective quality and user rating. Results: A total of 65 maternity-related nutrition and physical activity apps (34 from China and 31 from the United States) were eligible. Among them, 68% (21/31) of US apps and 56% (19/34) of Chinese apps did not provide supporting evidence for their content. A greater number of Chinese apps provided app-based general education modules, namely food nutrition knowledge (n = 0, 0% in the United States vs. n = 30, 88.2% in China). Meanwhile, a greater number of US apps provided exercise modules, namely pregnancy yoga (n = 21, 67.7% in the United States vs. n = 2, 5.9% in China). The objective app quality rating in the United States was lower than it was in China (mean: 3.5, SD: 0.6 in China vs. mean: 3.4, SD: 0.7 in the United States). There was no relationship between the overall objective quality rating and the user rating in either country. Conclusions: The characteristics and functional modules of in-store apps for maternal nutrition and physical activity differed between the United States and China. The results, therefore, suggest that user ratings cannot be used as an objective indicator of app quality and that it is necessary to improve the empirical basis and credibility of apps in both countries.